Compression moulding of Carbon/PEEK Randomly-Oriented Strands composites: A 2D Finite Element model to predict the squeeze flow behaviour. (February 2016) - Picher-Martel, Gilles-Philippe; Levy, Arthur; Hubert, Pascal
Abstract: Compression moulding of Randomly-Oriented Strands (ROS) of pre-impregnated thermoplastic composites is a process that enables the forming of complex parts with features such as ribs, thickness variations and holes in one single moulding step. This paper focuses on the macroscopic squeeze flow behaviour that occurs during forming. This mechanism rules the filling of intricate features of the mould initially empty. A 2D Finite Element model was developed to predict the squeeze flow of ROS composites. The material was modelled as a Bingham fluid and the equivalent viscosity and yield stress of three different strand sizes were determined using an inverse method. The viscosity and yield stress were found to increase with strand length. Experimental validation of the model was performed using Carbon/PEEK ROS flat samples and the average difference between experimentally measured and predicted final strain was below 5% for all cases.